Bombesin related peptides/receptors and their promising therapeutic roles in cancer imaging, targeting and treatment. (1st September 2016) - Moreno, Paola; Ramos-Álvarez, Irene; Moody, Terry W.; Jensen, Robert T.
ABSTRACT: Introduction: Despite remarkable advances in tumor treatment, many patients still die from common tumors (breast, prostate, lung, CNS, colon, and pancreas), and thus, new approaches are needed. Many of these tumors synthesize bombesin (Bn)-related peptides and over-express their receptors (BnRs), hence functioning as autocrine-growth-factors. Recent studies support the conclusion that Bn-peptides/BnRs are well-positioned for numerous novel antitumor treatments, including interrupting autocrine-growth and the use of over-expressed receptors for imaging and targeting cytotoxic-compounds, either by direct-coupling or combined with nanoparticle-technology. Areas covered: The unique ability of common neoplasms to synthesize, secrete, and show a growth/proliferative/differentiating response due to BnR over-expression, is reviewed, both in general and with regard to the most frequently investigated neoplasms (breast, prostate, lung, and CNS). Particular attention is paid to advances in the recent years. Also considered are the possible therapeutic approaches to the growth/differentiation effect of Bn-peptides, as well as the therapeutic implication of the frequent BnR over-expression for tumor-imaging and/or targeted-delivery. Expert opinion: Given that Bn-related-peptides/BnRs are so frequently ectopically-expressed by common tumors, which are often malignant and become refractory to conventional treatments, therapeutic interventions using novel approaches to Bn-peptides and receptors are being explored. Of particular interest is the potential of reproducing with BnRs in common tumors the recent success of utilizing overexpression of somatostatin-receptors by neuroendocrine-tumors to provide the most sensitive imaging methods and targeted delivery of cytotoxic-compounds.